Mentoring students of color : naming the politics of race, social class, gender, and power - Carrillo, Juan F.; Parker Moore, Danielle; Conder, Tim (Breakthroughs in the sociology of education, 2019)
"As more students of color continue to make up our nation's schools, finding ways to address their academic and cultural ways knowing become important issues. This book explores these intersections, by covering a variety of topics related to race, social class, and gender, all within a multiyear study of a mentoring program that is situated within U.S. K-12 schools. Furthermore, the role of power is central to the analyses as the contributors examine questions, tensions, and posit overall critical takes on mentoring. Finally, suggestions for designing critical and holistic programming are provided. Contributors are: Shanyce L. Campbell, Juan F. Carrillo, Tim Conder, Dana Griffin, Alison LaGarry, George Noblit, Danielle Parker Moore, Esmeralda Rodriguez, and Amy Senta"--